2014
DOI: 10.1182/blood-2014-03-564534
|View full text |Cite
|
Sign up to set email alerts
|

A Bim-targeting strategy overcomes adaptive bortezomib resistance in myeloma through a novel link between autophagy and apoptosis

Abstract: Key Points• Loss of Bim contributes to adaptive rather than intrinsic bortezomib resistance in multiple myeloma.• A Bim-targeting strategy combining an HDACI with a BH3 mimetic overcomes such resistance through a new link between autophagy and apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 67 publications
(102 reference statements)
6
73
0
Order By: Relevance
“…Combined treatment with panobinostat and FK506 enhanced cleavage of caspase-7 and -3 while increasing the BCL2-family protein BimS expression compared with panobinostat alone (Figure 4A). The previous study showed that Bim gene KO mouse embryo fibroblasts displayed diminished HDAC inhibitor-mediated apoptosis (36). These results suggest the importance of enhanced expression of Bim in HDAC inhibitor-mediated apoptosis and the possibility of blocking the effect of combined treatment with panobinostat and FK506 by shRNA Bim knockdown.…”
Section: The Effects Of Calcineurin Inhibition On Apoptosis and Prolimentioning
confidence: 86%
“…Combined treatment with panobinostat and FK506 enhanced cleavage of caspase-7 and -3 while increasing the BCL2-family protein BimS expression compared with panobinostat alone (Figure 4A). The previous study showed that Bim gene KO mouse embryo fibroblasts displayed diminished HDAC inhibitor-mediated apoptosis (36). These results suggest the importance of enhanced expression of Bim in HDAC inhibitor-mediated apoptosis and the possibility of blocking the effect of combined treatment with panobinostat and FK506 by shRNA Bim knockdown.…”
Section: The Effects Of Calcineurin Inhibition On Apoptosis and Prolimentioning
confidence: 86%
“…MM cell lines acquired drug resistance were generated as described earlier 28. Cells were cultured in a humidified incubator at 37°C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, Bim, known to be a key determinant of neoplastic cell sensitivity to various targeted agents (e.g. kinase inhibitors), has also been shown to be a significant factor in resistance of multiple myeloma cells to proteasome inhibitors [25] and of myeloid leukemia cells to histone deacetylase inhibitors [26]. Furthermore, activation of the multidomain pro-apoptotic proteins Bak and Bax play key roles in cell death regulation.…”
Section: Bcl-2 Family Proteins and Malignant Cell Survival And Resistmentioning
confidence: 99%
“…Among their numerous actions, HDACIs have been shown to upregulate expression of Bim through an E2F-dependent process [68]. Notably, HDACIs, when combined with BH3-mimetics such as ABT-737, effectively trigger apoptosis in multiple myeloma cells exhibiting either intrinsic or acquired resistance to bortezomib [25] through a process depending, at least in part, upon Bim upregulation. Whether similar effects occur in multiple myeloma cells exposed to venetoclax remains to be determined.…”
Section: Histone Deacetylase Inhibitors (Hdacis)mentioning
confidence: 99%